PENGARUH MOTIVASI, IKLIM KERJA DAN TINGKAT PENDIDIKAN TERHADAP PRODUKTIVITAS KERJA GURU SMK SARASWATI SUKOHARJO - Pratiwi, Sulastri (JURNAL MANAJEMEN SUMBER DAYA MANUSIA, 2015)
The purpose of this study to analyze the significance of the influence of motivation, work climate, the level of education on labor productivity Saraswati Sukoharjo vocational teachers. The study population was a vocational teacher Saraswati Sukoharjo. Sample of 40 respondents to the census techniques. The type of data using qualitative and quantitative data. Source of data using primary and secondary data. Documentation and data collection using questionnaires. Data were analyzed using multiple linear regression. The results of the study that motivation significant effect on labor productivity, labor climate significant effect on labor productivity and the level of education have a significant effect on the productivity of labor. Keywords: motivation, work climate, level of education, work productivity.